Evaluasi Kebijakan Penempatan Wilayah Kerja Pelabuhan Laut Pekanbaru Pada Balai Kekarantinaan Kesehatan Kelas I Pekanbaru - Rusydiana, Naila; Sujianto, Sujianto; As’ari, Hasim (Bahasa Indonesia, 2025)
This article aims to evaluate the success of the work area placement policy and identify obstacles that arise in the implementation of health quarantine surveillance activities in the Pekanbaru Sea Port work area, using the Daniel L. Stufflebeam (2017) CIPP evaluation model, namely Context to assess the suitability of program goals and objectives to the needs, Input to assess the adequacy of human resources, infrastructure, budget and regulations and Standard Operating Procedures (SOPs) that support, Process to assess the quality of programme implementation, compliance with schedules as well as staff involvement and use of facilities, Product to measure output in the form of a percentage of control of disease risk factors at the country's port of entry and outcome in the form of improved health quarantine services at the country's port of entry and region. This research uses descriptive evaluative research method using purposive sampling technique in determining informants. Data collection techniques through interviews, observations, document searches and documentation. The results of this study indicate that the policy of placement of the working area of the pekanbaru seaport has not succeeded in improving health quarantine services at the entrance to the country and region, this is due to the port relocation policy by the Ministry of Transportation not accompanied by changes in work area placement policies, limited human resources in implementing activities, lack of supporting infrastructure facilities operational and non-specific target data that makes it difficult to evaluate and planning.